2011
DOI: 10.1177/0957650911416914
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the tip clearance variation on the performance of a centrifugal compressor with considering impeller deformation

Abstract: The effects of impeller tip clearance variation on centrifugal compressor performance have been investigated experimentally and numerically in a centrifugal compressor. In order to accurately calculate the real tip clearance, the influence of impeller geometry deformation caused by the thermal load (temperature variation) and mechanical loads (aerodynamic pressure and centrifugal force) under working condition on the compressor aerodynamic performance is taken into account by fluid/solid interaction method dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…The trend in developing these new turbo shaft engines is to increase specific power with decreasing weight and volume. Another highly studied issue in recent years regarding the centrifugal compressor impeller is the influence of the tip clearance on the performance of the compressor [14]. It has been noticed that aerodynamics of the tip clearance plays an important role in the development of a centrifugal compressor and will have an important significance for the new engine models.…”
Section: Introductionmentioning
confidence: 99%
“…The trend in developing these new turbo shaft engines is to increase specific power with decreasing weight and volume. Another highly studied issue in recent years regarding the centrifugal compressor impeller is the influence of the tip clearance on the performance of the compressor [14]. It has been noticed that aerodynamics of the tip clearance plays an important role in the development of a centrifugal compressor and will have an important significance for the new engine models.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements performed by Wang et al [76] indicated that variations of tip clearance caused small influence on stall inception. However, the reasons could not be investigated because their mixing-plane, steady simulations failed to converge at near surge conditions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wang et al [76] used a two-step calculation procedure to take into account impeller deformation when simulating centrifugal compressor flow, avoiding a two-way coupled fluid-structure simulation. First, the deformation of the compressor blades were simulated with finite element method (FEM).…”
Section: Estimation Of Actual Tip Clearancementioning
confidence: 99%
See 2 more Smart Citations